11. Study of Beef Consumer Consideration Based On the Concept of Halal and Economic Factors in Butchery of Lambaro, Aceh Besar - Fuji Nuhraini; Teuku Reza Ferasyi; Rastina Rastina; Ismail Ismail; Nurliana Nurliana; Razali Razali (Universitas Syiah Kuala, 2018)
This study was aimed to determine the basic consideration of consumers based on halal and economic factors in beef markets (butchery) at Lambaro, Aceh Besar. A survey approach was used in this research through interview of respondents using structured questionnaire. The respondents were selected randomly from consumers purchased beef. The criteria of respondents were Muslim, aged≥ 20 years and purchased beef in the study location. The data obtained were analyzed descriptively. A number of 90 respondents were interviewed in this survey. The results showed that most of the consumers concerned about the halal aspect. Furthermore, a number of consumers stated that they expect for halal certificate available on the butchery. This is intended to increase consumer’s confidence on halal status of beef. Then, the economic factor also influenced the consumer’s choice for halal beef.